Community-based Ecological Citizenship Learning - Nisrina Nurul Insani; Diana Noor Anggraeni; Pitria Sopianingsih (CV. ULIL ALBAB CORP, 2025)
This research aims to respond to the urgent need to increase students' awareness and participation in environmental and social issues through the integration of the concept of ecological citizenship in civic education learning. The research method used is a qualitative approach with a case study method to explore in-depth understanding of the implementation of ecological citizenship integration and its impact on student civic engagement. The subjects of this research include lecturers, students, and communities. Data were collected through interviews, observations, and documentation studies. Interviews were conducted to explore views, experiences, and challenges in integrating ecological citizenship. Observation was used to observe classroom learning activities, while documentation study analysed learning materials and related projects. Data analysis showed that the integration of ecological citizenship significantly improved students' understanding and awareness of environmental responsibility, as well as encouraged their active participation in social and environmental activities.